Reassessment of branched Lithophyllum spp. (Corallinales, Rhodophyta) in the Caribbean Sea with global implications. Issue 6 (1st November 2016) - Hernandez-Kantun, Jazmin J.; Gabrielson, Paul; Hughey, Jeffery R.; Pezzolesi, Laura; Rindi, Fabio; Robinson, Nestor M.; Peña, Viviana; Riosmena-Rodriguez, Rafael; Gall, Line Le; Adey, Walter
Abstract: Plastid-encoded rbc L and psb A sequences from branched, Caribbean Sea Lithophyllum specimens indicate that four species are present, not one. Short (263 base pairs) rbc L sequences from an isolectotype of L. kaiseri (Gulf of Suez) and the holotypes of L. congestum, L. daedaleum and L. platyphyllum (Caribbean Sea) show that L. congestum and L. daedaleum are conspecific with L. kaiseri, the last having nomenclatural priority. Lithophyllum platyphyllum, currently considered a synonym of L. congestum, is recognised as a valid species. Lithophyllum stictaeforme, originally described from the Mediterranean Sea, is not conspecific with L. kaiseri (as L. congestum ) as previously suggested. Lithophyllum neocongestum sp. nov . and L. pseudoplatyphyllum sp. nov . are proposed. Together with L. platyphyllum, these three branched species are so far endemic to the Caribbean Sea. This is the first report, documented by DNA sequence data, of a coralline species ( L. kaiseri ) widespread through the tropical Indo-West Pacific Oceans, Red Sea and Caribbean Sea.